2019
DOI: 10.1093/forestry/cpz041
|View full text |Cite
|
Sign up to set email alerts
|

A practical measure for determining if diameter (D) and height (H) should be combined into D2H in allometric biomass models

Abstract: Tree diameter at breast height (D) and tree height (H) are often used as predictors of individual tree biomass. Because D and H are correlated, the combined variable D2H is frequently used in regression models instead of two separate independent variables, to avoid collinearity related issues. The justification for D2H is that aboveground biomass is proportional to the volume of a cylinder of diameter, D, and height, H. However, the D2H predictor constrains the model to produce parameter estimates for D and H … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
15
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(19 citation statements)
references
References 48 publications
2
15
0
2
Order By: Relevance
“…In the case of silver fir, the parameters showed quite a different pattern compared to European beech and other species. The scaling exponent of D (i.e., 1.33), surprisingly, was smaller than the scaling exponent of H (i.e., 1.45), showing a Q-ratio of 0.92 [54]. That means, in the case of silver fir, a 1% increase in D (while H constant) produced a 1.33% increase in AGB, whereas a 1% increase in H (under constant D) produced a 1.45% increase in AGB.…”
Section: Discussionmentioning
confidence: 86%
See 1 more Smart Citation
“…In the case of silver fir, the parameters showed quite a different pattern compared to European beech and other species. The scaling exponent of D (i.e., 1.33), surprisingly, was smaller than the scaling exponent of H (i.e., 1.45), showing a Q-ratio of 0.92 [54]. That means, in the case of silver fir, a 1% increase in D (while H constant) produced a 1.33% increase in AGB, whereas a 1% increase in H (under constant D) produced a 1.45% increase in AGB.…”
Section: Discussionmentioning
confidence: 86%
“…For models based on D and H, the scaling exponent of D was approximately 2.0, whereas the scaling exponent of H was smaller than 1.0 for most species [35]. Consequently, it has also been shown that the ratio between the parameter estimate of D and parameter estimate of H (i.e., the Q-ratio) is frequently larger than 2.0, usually between 3 and 4 [54]. In the case of silver fir, the parameters showed quite a different pattern compared to European beech and other species.…”
Section: Discussionmentioning
confidence: 99%
“…Parameter-parameter model regresi (a, b, c) ditentukan melalui analisis regresi non-linier menggunakan metode Generalized Non-linear Least Square (GNLS) yang efektif untuk mereduksi heteroskedastisitas ragam sisaan model (Pinheiro et al, 2020). Analisis regresi non-linier dilakukan menggunakan paket program nlme (Pinheiro et al, 2020) dalam software R versi 3.6.3 (R Core Team, 2020), karena paket program tersebut menerapkan metode GNLS untuk menghitung parameter model alometrik biomassa (Dutcă et al, 2019;Huy et al, 2016;Tiryana et al, 2011).…”
Section: Penyusunan Model Alometrik Biomassaunclassified
“…However, combining the variables D and H into D 2 H is not that harmless. Dutcă et al [18] showed that combining the variables into D 2 H can affect the accuracy of biomass prediction under certain conditions. They proposed a practical measure, the Q-ratio:…”
Section: Introductionmentioning
confidence: 99%
“…where β11 and β12 are the parameter estimates from Equation (1), to guide the decision as to whether D and H may be combined into D 2 H without the adverse effects of loss in biomass prediction accuracy. The authors showed that there is no preference in using a logtransformation or a weighted nonlinear approach to fit the allometric model (Equation ( 1)) in order to calculate the Q-ratio (Equation (3)), since the differences in estimated Q-ratio were minor [18]. The combined variable model (Equation ( 2)) is the equivalent of the separate variable model (Equation ( 1)), when Q = 2.0, and, therefore, the combined variable model can be safely used instead of separate variable model when Q = 2.0.…”
Section: Introductionmentioning
confidence: 99%